2015
DOI: 10.1021/acsami.5b08534
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetically Ornamented Rapid Prototyping Fabrication of an Apatite–Collagen–Polycaprolactone Composite Construct with Nano–Micro–Macro Hierarchical Structure for Large Bone Defect Treatment

Abstract: Biomaterial-based bone graft substitute with favorable mechanical and biological properties could be used as an alternative to autograft for large defect treatment. Here, an apatite-collagen-polycaprolactone (Ap-Col-PCL) composite construct was developed with unique nano-micro-macro hierarchical architectures by combining rapid prototyping (RP) fabrication technology and a 3D functionalization strategy. Macroporous PCL framework was fabricated using RP technology, then functionalized by collagen incorporation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 54 publications
2
81
0
Order By: Relevance
“…Therefore, scaffold-based polymer such as polycaprolactone (PCL) or polylactic acid (PLLA) were investigated for bone tissue engineering in recent years. [13][14][15] In vitro studies showed that a membrane system-based PCL can promote proliferation and early cell differentiation of osteoblast-like cells. 15 However, the disadvantage of the synthetic polymers is that it has a poor biocompatibility.…”
mentioning
confidence: 99%
“…Therefore, scaffold-based polymer such as polycaprolactone (PCL) or polylactic acid (PLLA) were investigated for bone tissue engineering in recent years. [13][14][15] In vitro studies showed that a membrane system-based PCL can promote proliferation and early cell differentiation of osteoblast-like cells. 15 However, the disadvantage of the synthetic polymers is that it has a poor biocompatibility.…”
mentioning
confidence: 99%
“…The nanofibers provided typical ECM to cells, where these cells formed endothelial monolayer with higher confluency. 67 In Figure 1b, Wang et al 68 developed apatite-collagen-polycaprolactone (Ap-Col-PCL) composites that showed excellent bioactivity to promote fast bone regeneration in rabbit model with fractional long bone defect. They combined rapid prototyping (RP) fabrication technology and 3D functionalization strategy for biomimetic deposition and collagen incorporation.…”
Section: Nanomaterials Applied In Bone Repair and Regenerationmentioning
confidence: 99%
“…These composite materials showed outstanding mechanical properties similar to cancellous bone, good biodegradability, and hierarchical architecture of three nano–micro–macro levels. 68 …”
Section: Nanomaterials Applied In Bone Repair and Regenerationmentioning
confidence: 99%
“…17 3) Fabricating functionally graded and multilayered membranes. 18 4) Incorporating osteoconductive calcium phosphate ceramics (eg, β-tricalcium phosphate, hydroxyapatite), 19,20 antibacterial agents (eg, metronidazole), bioactive proteins (eg, BMP-2), or growth factors (eg, stromal cell-derived factor-1α) into biodegradable polymers. 8,21 5) Modifying the biomembrane surface to graft bioactive molecules or proteins (eg, 3,4-dihydroxyphenylalanine [pDA]).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, COL I-pDA-PLGA/PCL ES membranes with interconnected pore networks may exhibit better mechanical function and better biological performance. 20 …”
mentioning
confidence: 99%